Nile River Basin modelling for water resources management – a literature review. Issue 1 (2nd January 2017) - Digna, Reem F.; Mohamed, Y. A.; van der Zaag, P.; Uhlenbrook, S.; Corzo, G. A.
ABSTRACT: Increasing water demand coupled with limited water resources has given rise to the need for sustainable water resources development in the Nile River Basin. Managing the basin's water resources is complex because of its transboundary nature, exacerbated by environmental degradation and strong climate variability. The Nile basin water resources have been extensively studied during the last 125 years for planning and management purposes, in particular with regard to the use of blue water in the downstream part of the basin, though recently some studies have also focused on the upper parts. These studies show that there is no convergence of development plans emerging among the Nile riparian countries. This paper reviews river basin water resource models as applied in the Nile River Basin, distinguishing between simulation, optimization and combined simulation and optimization models. The paper concludes by identifying knowledge gaps to guide future research on water resources planning and management in the Nile.